RETRACTED: Potential effects of elevated temperature on seasonal movements in slipper lobsters, Scyllarides latus (Latreille, 1803), in the eastern Mediterranean - GOLDSTEIN, JASON; SPANIER, EHUD (Mediterranean Marine Science, 2021)
Retraction of: Mediterranean Marine Science http://dx.doi.org/10.12681/mms.22074, published online 13 July 2020 Editor note: The authors are retracting this article. In the article, Potential effects of elevated temperature on seasonal movements in slipper lobsters, Scyllarides latus (Latreille, 1803), in the eastern Mediterranean (Vol. 21, 2020, https://doi.org/10.12681/mms.22074), authors J. Goldstein and E. Spanier have made an honest error in the inaccurate interpretation of their special scientific permit that afforded them the opportunity to collect wild-caught animals in the field and release them in their study area, in the marine reserve where this work was conducted. More specifically, the study component that refers to the ‘field tagging study’, was carried out without the full scope of permitting guidance unbeknownst to the authors. Dr. R. Yahel and E. Miller, Marine Ecologists of the Israeli National Park Authority (INPA), have pointed this out and have since requested that the article be removed given that the application of the special use permit was misinterpreted and not exercised in an appropriate manner. The authors were also not able to forward the INPA with the field’s raw data that have been lost since this field study was carried out over eight years ago. The authors were not aware of this discrepancy at the time the field study was carried out, but they have agreed to remove the article out of respect and admiration of the INPA and the continued protection and conservation of the Mediterranean slipper lobster in coastal Israeli waters. However, this action of retraction does not change the overall outcome of the paper’s finding including the study design, analyses, scientific integrity, or overall conclusions. The authors will plan on publishing the laboratory-based portion of this study as a stand-alone manuscript at a future date.